Perceptual Distortions of 3-D Finger Size. (August 2019) - Tavacioglu, Ebru Ecem; Azañón, Elena; Longo, Matthew R.
Our body is a volumetric, three-dimensional (3-D) object in the world, and we experience it as such. Existing methods for measuring the perceptual body image, however, have been based on judgments of one-dimensional (1-D) length or two-dimensional images. We developed a new approach to the 3-D perceptual body image of the fingers by asking people to judge whether each finger would fit through rings of varying diameter. This task requires participants to conceptualize their finger as a volumetric object entering the ring. In two experiments, we used an adaptive staircase procedure to estimate the perceived size of each finger. There were systematic distortions of perceived 3-D finger size, with the size of index finger and (to a lesser extent) the middle finger underestimated. These distortions were unaffected by changes in hand posture. Notably, the pattern of distortions is qualitatively different from that found in previous research investigating 1-D finger length, suggesting that 3-D judgments of the body may differ in fundamental ways from 1-D judgments of individual body dimensions.